DAMPAK PERNIKAHAN DINI DALAM PERSPEKTIF HUKUM ISLAM DI DESA SINGKI KECAMATAN ANGGERAJA KABUPATEN ENREKANG - Muh. Muhsin; Akmal Fauzan; Nurul Aulia Putri; Riska Perhana Jaya (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2025)
This research aims to find out Islamic views on early marriage because early marriage can hamper children’s education an can also disrupt mental health because in reality early marriage will have an impact on the child which will affect personal and social life. According to the author, several factors of early marriage it varies greatly, including because of economic factors, because of arranged marriages and also because of local habits or costoms. Considering the risks that need to be taken into account, early marriage is also considered as a fulfilment of the Sunnah and an offertto maintain morality wchich is seen from a positive perspective for individuals whoo are not yet fully mature. Emotional in terms of financesand financial responsibilility. Women must have their rights guaranteed so that inequality does not occur. That is why it is very important to evaluate early marriage carefully to ensure proper understanding regarding individual readiness and human rights. This research uses qualitative metodhes.